2021
DOI: 10.1002/jts.22781
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cognitive behavioral conjoint therapy for posttraumatic stress disorder (PTSD) in a U.S. Veterans Affairs PTSD clinic

Abstract: Cognitive behavioral conjoint therapy (CBCT) for posttraumatic stress disorder (PTSD) is a 15-session conjoint treatment for PTSD designed to improve PTSD symptoms and enhance intimate relationship functioning. Numerous studies of CBCT for PTSD document improvements in patient PTSD and comorbid symptoms, partner mental health, and relationship adjustment. However, little is known about its effectiveness in real-world clinical settings. Using an intentionto-treat sample of couples who participated in CBCT for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
22
1
Order By: Relevance
“…Importantly, both bCBCT and PFE produced improvements in functional impairment and relationship satisfaction, though counter to our hypotheses, bCBCT was not statistically superior to PFE on these outcomes. Completion rates in the present study (70%) were on par with prior smaller trials of the 15-session CBCT protocol (Liebman et al, 2020) but much higher than a recently published CBCT study in a VA PTSD clinic where completion rates where 52% (Pukay-Martin et al, 2021) and individual PTSD treatment in the VA where completion rates were reported in a recent large trial to be approximately 44% for PE and 53% for CPT (Schnurr et al, 2022). Unexpectedly, both completion and treatment process metrics were similar across the three treatment arms, with the exception of partners’ treatment satisfaction and working alliance, which were significantly higher in OB-PFE than in HB-bCBCT.…”
Section: Discussioncontrasting
confidence: 53%
“…Importantly, both bCBCT and PFE produced improvements in functional impairment and relationship satisfaction, though counter to our hypotheses, bCBCT was not statistically superior to PFE on these outcomes. Completion rates in the present study (70%) were on par with prior smaller trials of the 15-session CBCT protocol (Liebman et al, 2020) but much higher than a recently published CBCT study in a VA PTSD clinic where completion rates where 52% (Pukay-Martin et al, 2021) and individual PTSD treatment in the VA where completion rates were reported in a recent large trial to be approximately 44% for PE and 53% for CPT (Schnurr et al, 2022). Unexpectedly, both completion and treatment process metrics were similar across the three treatment arms, with the exception of partners’ treatment satisfaction and working alliance, which were significantly higher in OB-PFE than in HB-bCBCT.…”
Section: Discussioncontrasting
confidence: 53%
“…However, studies of CBCT have tended to find improvements in partner depression and anxiety, particularly for those with higher initial symptoms (Shnaider et al., 2014), whereas improvement in partner anger has not been observed (see Liebman et al., 2020 for a review). Moreover, a recent open trial of CBCT in the U.S. Department of Veterans Affairs health care system found significant improvement in partner depression despite partners starting in the mild range (Pukay‐Martin et al., 2022). More research is needed with larger samples to estimate the effect of Couple HOPES on partner mental health more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Given the negative impact of PTSD on relationships and the well‐being of romantic partners, conjoint interventions that target all of these domains, such as cognitive behavioral conjoint therapy (CBCT; Monson & Fredman, 2012), may be particularly promising. Research has demonstrated that CBCT is effective in improving PTSD symptoms and relationship satisfaction in individuals with PTSD, as well as their partners’ relationship satisfaction, relationship happiness, and depressive and anxiety symptoms (Liebman et al., 2020; Pukay‐Martin et al., 2022). However, significant barriers impede access to face‐to‐face evidence‐based treatments, including limited numbers of trained clinicians, geographical distance, scheduling, and perceived stigma (Kazdin & Blase, 2011), all of which have been exacerbated by the COVID‐19 pandemic.…”
mentioning
confidence: 99%
“…14,17 Lastly, CBCT is 15 sessions and is designed to treat PTSD in a couples setting using principles of cognitive behavioral therapy applied to the couple. [17][18][19] In order to understand the utilization of these therapies and test whether participation in each was associated with better outcomes in PTSD treatment, the current study used VHA electronic health record (EHR) data to address 2 research questions. (1) What family therapies are veterans diagnosed with PTSD using?…”
Section: Introductionmentioning
confidence: 99%